Multimodal Analysis: Revealing Bayu Skak’s Frustration in “Valentine Janc#k” Video - Natasya Evelyn Alamsyah (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This qualitative study aimed to know the meaning of an expression especially Bayu’s expressions in this “Valentine Janc#k” video. Expression is something that cannot be separated from a conversation. The expression itself has various meanings; sometimes the same expression can have two or even more meanings. To get the accurate meaning, all aspects within us must work together such as: facial expressions, gesture, and also the choice of words used. Just like what the writer found in this "Valentine Janc#k" video, where Bayu shows an expression like being angry which the writer then follows up to get the accurate meaning. In doing so, the writer uses a multimodal theory which focuses on semiotic modes such as linguistic modes, gestural modes, and visual modes. Then, the writer found out that all of the facial expressions, gestures, and also the setting of the place that the writer analyzes in the video show signs of expression that lead to frustration. When talking about Valentine, Bayu shows an annoyed and unpleasant facial expression, the body movements shown by Bayu also show disinterest in the topic of conversation, as well as a messy viewpoint which describes Bayu's messed feelings for Valentine. The choice of words Bayu uses against Valentine (swear words) also plays a big role in showing the frustration. Keywords: multimodal, semiotic modes, lingustic modes, gestural modes, visual modes